Pengaruh Suasana Toko dan Lokasi Terhadap Kepuasan Konsumen dan Dampaknya Keputusan Pembelian (Survey pada Konsumen Seblak Pedas Neng Ochie) - Santharia Mercelina; Joseph M.J. Renwarin (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of store atmosphere and location on consumer satisfaction and its impact on purchasing decisions survey on consumers as spicy as neng Ochie. This research is quantitative method research. The sample is consumers of seblak spicy nengochie with a total sampel 200 respondents. The sampling technique uses non-probability sampling with purposive sampling technique. Hypotesisis testing method using t test and linear regression test. The results of this study indicate that the shop atmosphere has significant effect on customer satisfaction. Location has a significant effect on customer satisfaction. Store atmosphere and location have a positive and significant effect simultaneously on customer satisfaction, storeatmosphere, location and customer satisfaction have a significant effect on purchasing decisions, shop atmosphere through consumer satisfaction with purchasing decisions. Location through consumer satisfaction with purchasing decisions.